Targeting your audience: wildlife value orientations and the relevance of messages about bear safety. Issue 3 (4th May 2018) - Miller, Zachary D; Freimund, Wayne; Metcalf, Elizabeth Covelli; Nickerson, Norma
ABSTRACT: While there is an assumption that wildlife value orientations can be useful in strategic communication, few studies have empirically explored this topic. This article used the concept of wildlife value orientations to understand how to increase the motivation of people to process information about wildlife in the context of persuasive communication. A confirmatory factor analysis was used to identify mutualism and domination wildlife value orientations. From the wildlife value orientations, crosstabs were used to create a typology with four discreet segments: mutualists, pluralists, traditionalists, and distanced. A series of ANOVAs examined how important different messages about bear safety were to the typology segments. Results indicated that message relevancy differs among wildlife value orientations. Managers can use this information to help frame their communications about wildlife-related issues. Future research should continue to explore the impact of this value-framing approach to other persuasive communication concepts, like attitudes and behaviors.